2016
DOI: 10.1038/mt.2015.224
|View full text |Cite
|
Sign up to set email alerts
|

Glycolate Oxidase Is a Safe and Efficient Target for Substrate Reduction Therapy in a Mouse Model of Primary Hyperoxaluria Type I

Abstract: Primary hyperoxaluria type 1 (PH1) is caused by deficient alanine-glyoxylate aminotransferase, the human peroxisomal enzyme that detoxifies glyoxylate. Glycolate is one of the best-known substrates leading to glyoxylate production, via peroxisomal glycolate oxidase (GO). Using genetically modified mice, we herein report GO as a safe and efficient target for substrate reduction therapy (SRT) in PH1. We first generated a GO-deficient mouse (Hao1(-/-)) that presented high urine glycolate levels but no additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
101
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(107 citation statements)
references
References 17 publications
6
101
0
Order By: Relevance
“…Recent results reported by Martin-Higueras et al 13 support the therapeutic potential for ALN-GO1 to profoundly lower oxalate levels in patients by silencing HAO1 mRNA. In these studies, GO-deficient mice (Hao1 2 /2 ) exhibit asymptomatic glycolate elevation, but no phenotypic differences in urine sediment, crystal deposition, histology, or breeding.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Recent results reported by Martin-Higueras et al 13 support the therapeutic potential for ALN-GO1 to profoundly lower oxalate levels in patients by silencing HAO1 mRNA. In these studies, GO-deficient mice (Hao1 2 /2 ) exhibit asymptomatic glycolate elevation, but no phenotypic differences in urine sediment, crystal deposition, histology, or breeding.…”
Section: Discussionmentioning
confidence: 69%
“…In fact, as recently described, crossing GO-deficient mice (Hao1 2/2 ) into the AGXT deficient background nearly resolved disease, with oxalate levels near normal, indicating the near total dependence of this pathway in mice on GO. 13 Rodents have evolved with AGTexpressed in both mitochondria and peroxisomes in contrast to only a peroxisomal localization in humans, suggesting that glyoxylate production in rodent mitochondria may be significant. As a result, mice lacking mitochondrial AGT will excrete greater amounts of glyoxylate produced in the mitochondria into the cytosol compared with wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This cycling most likely plays an important role in the pathophysiology of PH1, due to the hydrogen peroxide produced with each cycle. Recent studies by our group and others have shown that reducing GO activity with siRNA in the Agxt-deficient mouse results in a significant decrease in urinary oxalate excretion, 19,31,32 further supporting that glycolate metabolism is a major source of oxalate in PH1, independent of Hyp catabolism. Subsequent work with rats and monkeys 33 further supported GO as a viable siRNA knock down target for oxalate reduction therapy, and clinical trials in patients with PH1 using GO siRNA are being conducted.…”
Section: Hyp Metabolismmentioning
confidence: 64%